2021
DOI: 10.17998/jlc.21.1.69
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Lymphocyte-Rich Hepatocellular Carcinoma in a Patient Who Was Treated for Colon Cancer

Abstract: Hepatocellular carcinoma (HCC) primarily originates in the liver with hepatic differentiation. However, HCCs are not homogenous, and approximately 35% of HCC cases are classified as histopathological variants that present distinct pathologic characteristics. In particular, the lymphocyte-rich variant is the rarest subtype accounting for less than 1% of HCCs, which is not well known to date about molecular features and pathophysiology. Herein, we present a case of a patient who was suspected of metastatic liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Although typical molecular alterations for this variant are not clear, this variant has shown to have high PD-L1 expression. 9,10 To the best of our knowledge, we present first ever reports of FNAC of steatohepatitic variant and lymphocyte-rich variant of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Although typical molecular alterations for this variant are not clear, this variant has shown to have high PD-L1 expression. 9,10 To the best of our knowledge, we present first ever reports of FNAC of steatohepatitic variant and lymphocyte-rich variant of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…As many as 35% of HCCs are classified into histopathologic variants by clinicopathologic and molecular characteristics 8,23,47 . Recent studies have demonstrated a good correlation between the histologic subtypes and gene mutations: CTNNB1 ‐mutated HCCs with large, well‐differentiated, cholestatic with microtrabecular and pseudoglandular histology; TP53 ‐mutated HCCs with poorly differentiated compact pattern with pleomorphic cells and frequent vascular invasion, scirrhous subtype with TSC1/TSC2 mutations, epithelial to mesenchymal transition; steatohepatitic subtype with frequent IL‐6/JAK/STAT activation without CTNNB1, TP53 and TERT alterations; and macrotrabecular massive subtype with high AFP level, TP53 mutations, FGF19 amplifications, vascular invasion and poor survival 48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…As many as 35% of HCCs are classified into histopathologic variants by clinicopathologic and molecular characteristics. 8,23,47 Recent studies have demonstrated a good correlation between the histologic subtypes and gene mutations: CTNNB1-mutated HCCs with large, well-differentiated, cholestatic with microtra-…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation